In Vitro Application of Sonodynamic Antimicrobial Chemotherapy as a Sonobactericidal Therapeutic Approach for Bacterial Infections: A Systematic Review and Meta-analysis: Sonodynamic Antimicrobial Chemotherapy Against Microbial Infections - Pourhajibagher, Maryam; Bahador, Abbas (Journal of Lasers in Medical Sciences, 2020)
Introduction: This study aimed to perform a systematic review of the literature followed by a meta-analysis about the efficacy of sonodynamic antimicrobial chemotherapy (SACT) in bacterial infections. Methods: According to the PICOS (population, intervention, comparison, and outcome) recommendations and PRISMA guidelines, an electronic search was conducted in PubMed, SCOPUS, Embase, and Cochrane Library based on the MeSH terms. All analyses were conducted using Biostat’s Comprehensive Meta-Analysis version 2.0. The inter-study heterogeneity and publication bias assessments were carried out on the studies using I2 and Egger’s regression test. Results: Initially, 126 articles were identified in the electronic search, and 14 studies remained after analysis and exclusion of the duplicated studies and eligibility criteria. All results from the included studies displayed a significant reduction of microorganisms. The meta-analysis demonstrated a significant reduction in the bacterial load in all analyses (0.944% [95% CI, 0.901-0.969%; P=0.000]). Also, there was a low risk of bias for microbial load reduction without the evidence of publication bias. Conclusion: The results highlight that there is scientific evidence emphasizing the effectiveness of SACT in reducing the count of microorganisms in bacterial infections.